2016
DOI: 10.4103/0377-4929.182013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four different methods for detection of biofilm formation by uropathogens

Abstract: TCP method is the ideal method for detection of bacterial biofilm formation by uropathogens. MCRA method is superior only to CRA for detection of staphylococcal biofilm formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 0 publications
6
19
5
Order By: Relevance
“…Maximum positivity was seen by Microtiter plate method with 58.33% moderate biofilm producers and 3.33% strong biofilm producers whereas tube adherence method showed only 2.33% strong biofilm producers and 45.00% moderate biofilm producers. Similar results were also produced by Mathur et al and Panda et al (19) Also, all the above observers found the biofilm production in one type of strain of bacteria, but in the current study it was proved in five different strains of bacteria.…”
Section: Discussionsupporting
confidence: 91%
“…Maximum positivity was seen by Microtiter plate method with 58.33% moderate biofilm producers and 3.33% strong biofilm producers whereas tube adherence method showed only 2.33% strong biofilm producers and 45.00% moderate biofilm producers. Similar results were also produced by Mathur et al and Panda et al (19) Also, all the above observers found the biofilm production in one type of strain of bacteria, but in the current study it was proved in five different strains of bacteria.…”
Section: Discussionsupporting
confidence: 91%
“…P. aeruginosa PAO1 biofilms were quantified based on the tube method (Panda et al, 2016). Overnight, P. aeruginosa cultures were diluted 1:50 into 200 μL of Trypticase Soytone broth (TSB, 1.7% tryptone, 0.3% soy protone, 0.25% glucose, 0.5% NaCl, 0.25% KH 2 PO 4 , pH 7.2, OD 620 ≈ 0.1; Cycoń et al, 2016) with varying concentrations of extract.…”
Section: Methodsmentioning
confidence: 99%
“…Optical densities values indicated bacterial adherence to the wells and biofilm formation. The OD values were calculated and biofilm production was graded into strong, moderate and non/weak (Table 1) as described in previous studies (2,(12)(13)(14).…”
Section: Tissue Culture Plate Methodsmentioning
confidence: 99%
“…Bacteria tend to live in a community-like assembly called biofilm. Development of bacterial biofilms occurs in a dynamic process that includes bacterial attachment to a particular surface, irreversible binding and formation of a hydrated matrix of polysaccharides and protein (1,2). Surfaces that favor biofilm development include inert surfaces as medical devices and dead tissues as dead bone fragments (1,3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation